2001
DOI: 10.1352/0895-8017(2001)106<0434:smpocf>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Staff Members' Prediction of Consequences for Their Work in Residential Settings

Abstract: Staff members supporting people with mental retardation in residential care were given scenarios describing tasks they might carry out and asked what would happen if they did, or failed to do, them (i.e., who would notice, what would their reaction be). Only a minority reported strong, certain consequences for anything they did from residents, families, or external professionals. Although a majority reported consequences from managers or coworkers, a large minority did not. The tasks for which most staff membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…For example, Mansell et al (1994) proposed that managers need to give staff clear and consistent messages about the expectation that their practice will reflect organizational values that put service user quality-of-life outcomes at the centre of everything they do. While there is no evidence to support this proposition, Mansell & Elliott (2001) found that onesixth of staff said that they thought no one would notice what they did with service users -good or bad, and that the activity with the biggest consequences from managers was whether they were completing the paperwork correctly. More particularly, there are propositions about the positive influence, in terms of improving and maintaining good staff practice, if front-line management incorporates all or some of the elements of practice leadership.…”
Section: Managerial Practicementioning
confidence: 99%
“…For example, Mansell et al (1994) proposed that managers need to give staff clear and consistent messages about the expectation that their practice will reflect organizational values that put service user quality-of-life outcomes at the centre of everything they do. While there is no evidence to support this proposition, Mansell & Elliott (2001) found that onesixth of staff said that they thought no one would notice what they did with service users -good or bad, and that the activity with the biggest consequences from managers was whether they were completing the paperwork correctly. More particularly, there are propositions about the positive influence, in terms of improving and maintaining good staff practice, if front-line management incorporates all or some of the elements of practice leadership.…”
Section: Managerial Practicementioning
confidence: 99%
“…employing and external agencies) provide expectations and consequences that focus upon formal administrative work potentially leaving little space for PL e.g. working with staff to develop AS (Mansell & Elliott, 2001;Lowe & Jones, 2006). Research focussed upon the incentive context for RM would be useful.…”
Section: Informal Interactional Versus Formal Organisational Systemsmentioning
confidence: 99%
“…Anecdotal evidence suggests that increased resident engagement can be motivating for staff, although other evidence indicates that staff may experience consequences from management for paperwork rather than for enabling resident activity (Mansell & Elliott, 2001). One potentially important issue is the resident engagement ''payoff'' for staff assistance: how much resident engagement is obtained for one unit of staff assistance?…”
Section: Distribution Of Staff Assistancementioning
confidence: 99%